State legislation and policies to improve perinatal mental health: a policy review and analysis of the state of Illinois - Tabb, Karen M.; Hsieh, Wan-Jung; Ramirez, Xavier R.; Kopels, Sandra (Frontiers in Psychiatry, 2024)
Maternal mental health problems, such as perinatal depression, are a major public health issue. In the U.S., several states have policies related to mental health during pregnancy and postpartum. The extent of these laws at the state level needs to be further explored and described. We systematically searched the Illinois General Assembly to determine all existing legislation on the topic of perinatal mental health. This search uncovered two major Acts that 1) require universal perinatal depression screening and 2) raise awareness of the symptoms and treatment options related to maternal mental health. We also discovered provisions in the law that allow for untreated or undiagnosed postpartum depression or psychosis to be considered as a mitigating factor for women who commit forcible felonies. Through legislation, states can lead change at the systems-level to improve perinatal mental health outcomes.